Pendekatan Simulasi Monte Carlo Untuk Pemilihan Alternatif Dengan Decision Tree Pada Nilai Outcome Yang Probabilistik - Winda Nur Cahyo (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
Tree Diagram has been familiarly known as one of the tools used to solve or to make decision forproblems that have some alternatives of solutions. But usually the outcome of the diagram aredeterministicly approached. This paper suggested Monte Carlo Simulation to approach the deterministicaspect of outcome to become probabilistic. But there are some asumtions of the diagram must be changeto adjust the Monte Carlo Approach.Keywords: Tree Diagram, Monte Carlo Simulation, Decision Analysis.